Benefits of task-based language teaching method in developing ESL students speaking skills - Azman, Ain Syafiqah Balqis (Human Resource Management Academic Research Society, 2023)
Task-based language teaching alludes to a communicative approach in which it is grounded on the utilization of real-life and pedagogical tasks as the central element for language instruction. Hence it has become an important topic in the field of second language acquisition in respect of fostering process-focused syllabi and developing communicative tasks to enhance learners’ use of language. This study aims to provide researchers and educators with the compositions of evidence gathered in previous relevant papers on ESL learners’ challenges in speaking English and exploring the benefits of Task-Based Language Teaching for ESL learners’ speaking skills. The result of this study indicates that with the usage of TBLT, teachers are exposed more towards the variation of communicative tasks that cater not only for students' needs but also enhance their creativity through the diversity of tasks that draws out the student’s utmost capability.